2005
DOI: 10.1136/adc.2003.047530
|View full text |Cite
|
Sign up to set email alerts
|

Adenotonsillectomy for upper respiratory infections: evidence based?

Abstract: Background: Despite high rates of (adeno)tonsillectomy for upper respiratory infections in western countries, the medical literature offers the physician little support in deciding which child might benefit from the operation. Methods: A literature search was performed to identify randomised trials and non-randomised controlled studies into the efficacy of tonsillectomy with or without adenoidectomy in children under 18 years. For the outcomes sore throat episodes, sore throat associated school absence, and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 29 publications
5
52
0
2
Order By: Relevance
“…accepted guidelines on the indications for this procedure are available [5,6]. Respiratory disease in children, including infections, are among the most important public health problems [7]. Many factors are involved in the recurrence of disease as such as genetic, environmental and host predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…accepted guidelines on the indications for this procedure are available [5,6]. Respiratory disease in children, including infections, are among the most important public health problems [7]. Many factors are involved in the recurrence of disease as such as genetic, environmental and host predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…Adeno/tonsillectomy leads to an additional, but small, reduction of sore throat episodes, days of sore throat associated school absence, and upper respiratory infections, compared to watchful waiting (15). This research showed that there was a highly statistically significant association between adenotonsillar infections and antibiotic therapy with acute otitis media.…”
Section: Discussionmentioning
confidence: 57%
“…7 It is believed that this small benefit is offset by the increased morbidity associated with surgery and the higher cost of treatment. 8,9 Hence, the current practice in England is that of watchful waiting.…”
Section: Introductionmentioning
confidence: 99%